Une nouvelle source pour l’histoire du monastère de la Croix-Saint-Ouen à la fin du IXe siècle - Jacques Le Maho (Tabularia)
In a letter written between 885 and 890 by Gautier, bishop of Orléans, to Lambert, bishop of Le Mans, Gautier asks his correspondent to greet favourably a party of monks fleeing the Northmen and about to leave Orléans to go back to the earldom of Bayeux. Bernhard Bischoff, the first to publish the text, thought these monks could be identified with those of Saint-Ouen in Rouen, but they are most probably friars from Croix-Saint-Ouen, today’s La Croix-Saint-Leufroy in the Euredepartment. Gautier’s letter thus enables us to know a little more about that community between 884, when king Carloman II confirmed what accrued to it through the monastery custom, and 918, when Charles the Simple bestowed the last remnants of his patrimony on Saint-Germain-des-Prés abbey.